Effects of opium inhalation on pulmonary volumes in smoking patients - Fadaii, Abbas; Sohrabpour, Hamid; Taherkhanchi, Bahar; Seddighi Moghdaam, Hamid Reza; Bagheri, Bahador (Archives of Advances in Biosciences, 2015)
Historically, opium was used as a potent analgesic and to treat dyspnea and cough. It is documented that opium can increase exercise tolerance and relieve breathlessness. However, its overdose can suppress respiratory centers. The purpose of this study was to evaluate effects of opium on spirometric lung volumes.The study was done on two groups of patients referred to the lung clinic of Labbafi Nejad hospital. Group A was composed of 84 patients who were smokers and group B was made up of 40 patients who were smokers and opium addicts. Patients underwent spirometry and demographic questionnaires were collected. Significant differences were noted on lung volumes between two groups. Forced Vital Capacity (FVC) was 56 ± 4.6 % in Group A and 72 ± 4.7 % in Group B (P < 0.001). Difference on Forced Expiratory Volume in one second (FEV1) was also statistically significant, 53 ± 6.6 % in Group A versus 69 ± 4.4 % in Group B (P < 0.001). In this study, lung volumes were considerably larger in patients who were opium addicts and smokers compared to patients who were only smokers. Further studies are warranted to confirm these results, and such confirmation may lead to better understanding about role of opioids in respiratory diseases.